Acute exacerbation of idiopathic pulmonary fibrosis triggered by Aspergillus empyema. (2018) - Suzuki, Atsushi; Kimura, Tomoki; Kataoka, Kensuke; Matsuda, Toshiaki; Yokoyama, Toshiki; Mori, Yuta; Kondoh, Yasuhiro
Abstract: Acute exacerbation (AE) is a severe and life-threatening complication of idiopathic pulmonary fibrosis (IPF). In 2016, the definition and diagnostic criteria for AE-IPF were updated by an international working group. The new definition includes any acute, clinically significant respiratory deterioration (both idiopathic and triggered events) characterized by evidence of new widespread alveolar abnormality in patients with IPF. There are no currently proven beneficial management strategies for idiopathic and triggered AE-IPF. This is the first report describing AE-IPF triggered by Aspergillus empyema, which was improved by a combination of corticosteroid, systemic antifungal therapy, local antifungal therapy, and additional pharmacological therapies. Future research may reveal optimal strategies for both idiopathic and triggered AE-IPF.